2022
DOI: 10.1096/fj.202200314r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical force modulates macrophage proliferation via Piezo1‐AKT‐Cyclin D1 axis

Abstract: Orthodontic tooth movement (OTM) is induced by biomechanical stimuli and facilitated by periodontal tissue remodeling, where multiple immune cells participate in this progression. It has been demonstrated that macrophage is essential for mechanical force‐induced tissue remodeling. In this study, we first found that mechanical force significantly induced macrophage proliferation in human periodontal samples and murine OTM models. Yet, how macrophages perceive mechanical stimuli and thereby modulate their biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
(84 reference statements)
1
18
0
Order By: Relevance
“…Mice were given the TGF‐β receptor I, II inhibitor (LY‐364947, Med Chem Express) intraperitoneally at a dose of 10 mg/kg body weight in a solution of 200 μL of 5% DMSO and 95% sunflower seed oil (Vehicle). GsMTx4 (Med Chem Express) was previously dissolved in ddH 2 O and then administered to mice as a 10 μL (5 μM) intraperitoneal injection 20 . Following the mice's exercise, drugs were given once every 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were given the TGF‐β receptor I, II inhibitor (LY‐364947, Med Chem Express) intraperitoneally at a dose of 10 mg/kg body weight in a solution of 200 μL of 5% DMSO and 95% sunflower seed oil (Vehicle). GsMTx4 (Med Chem Express) was previously dissolved in ddH 2 O and then administered to mice as a 10 μL (5 μM) intraperitoneal injection 20 . Following the mice's exercise, drugs were given once every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the manufacturer's recommendations, RAW 264.7 cells were transiently transfected in six‐well plates with Piezo1 siRNA at a final concentration of 100 nM using Opti‐MEM (Gibco) supplemented with Lipofectamine 2000 Reagent (Invitrogen). We refer to the sequences of other subject groups 20 : Piezo1‐siRNA, 5′‐AGGAAGAAGCCAGAAGCUAATT‐3′ and 5′‐UUAGCUUCUGGCUCUUCCUTT‐3′, negative control (NC)‐siRNA, 5′‐UUCUCCGAACGUGUCACGUTT‐3′ and 5′‐ACGUGACACGUUCGGAGAATT‐3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow-derived macrophages express high levels of Piezo1, which can be activated by mechanical stimulation to trigger a proinflammatory response (Solis et al, 2019). Using both human PDL samples and OTM mouse models, a recent study found that mechanical force induces macrophage proliferation via the Piezo1-AKT-cyclin D1 axis (Xu et al, 2022). Moreover, inhibition of Piezo1 by GsMTx4 effectively inhibits tensile stressinduced macrophage proliferation and thus suppresses OTM.…”
Section: Piezo Channels In Periodontal Bone Remodeling and Orthodonti...mentioning
confidence: 99%
“…Piezo1 and Piezo2 have also been reported to affect the skeletal system, and Piezo1 deficiency has been shown to impair bone anabolism and induce abnormal responses to external forces (Li et al, 2019;Sun et al, 2019;Wang et al, 2020;Zhou et al, 2020). Furthermore, emerging evidence indicates that Piezo1 and Piezo2 help to regulate dental pain and participate in signaling transduction in dental-derived stem cells, periodontal bone remodeling and orthodontic tooth movement (OTM) (Gao et al, 2017;Sugimoto et al, 2017;Won et al, 2017;Jiang et al, 2021;Cho et al, 2022;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%